Engineering applications of neural networks : 19th International Conference, EANN 2018, Bristol, UK, September 3-5, 2018, Proceedings /: 19th International Conference, EANN 2018, Bristol, UK, September 3-5, 2018, Proceedings. (2018) - Unknown
No abstract available